HEADACHES IN CHILDREN AND ADOLESCENTS: CLINICAL PECULIARITIES AND PROPHYLAXIS - N.N. Zavadenko; Yu.E. Nesterovskiy ("Paediatrician" Publishers LLC, 2011)
The publication gives a review of clinical peculiarities and prophylactic methods of initial headaches in children and adolescents: migraines and stress headaches. Modified and unmanageable trigger factors of migraine are analyzed; different methods of headaches prophylaxis are discussed.Key words: initial headaches, children, adolescents, prophylaxis, ultrasonic Doppler analysis.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 162-169)